Early pregnancy outcomes in East African Shorthorn Zebu cattle synchronized with 5 progesterone-based Co-synch protocol modifications - Patrick Mawadri; Shadia Kantono; Denis Mugizi; Benon Kanyima; David Okello-Owiny; Maria Nassuna-Musoke; Charles Lagu; James Okwee-Acai (Clinical Theriogenology, 2026)
Estrus and ovulation synchronization optimize artificial insemination and accelerate livestock productivity improvement by enhancing reproductive performance. However, available protocols are suboptimal in Bos indicus cattle, justifying search for novel protocols. We evaluated the effects of 5 synchronization protocols on conception rates in 232 Shorthorn Zebu cows. The protocols were: 7-day Co-synch + progesterone intravaginal device (P4ID); n = 40); Bee-Synch I (n = 44); Bee-Synch II (n = 42); Mak-Synch I (modification of 7-day Co-synch + P4ID that extends the time for GnRH-2 and timed AI from 60-66 to 74-78 hours, respectively; n = 52); and Mak-Synch II (a modification of Bee Synch II that extends the time for GnRH-2 and timed AI from 64-68 to 74-78 hours, respectively; n = 54). Pregnancy status was determined on day 32 via transrectal ultrasonography. A multiple logistic regression model was used to compare mean conception rates among protocols at the 95% confidence level in R. Adjusted mean (± standard error) conception rates were 44.59 ± 9.38%, 37.26 ± 8.48%, 42.09 ± 8.86%, 57.84 ± 8.42% and 47.19 ± 7.76% for 7-day Co-synch + P4ID, Bee-Synch I, Bee-Synch II, Mak-Synch I and Mak-Synch II protocols, respectively, not different (p > 0.05) among protocols. Compared to cows with body condition score (BCS) 2.5, there were significantly higher odds of conception in those with BCS 3.0 (OR = 4.24, 95% CI: 1.19-20.2, p = 0.039), BCS 3.5 (OR = 5.45, 95% CI: 1.46-26.8, p = 0.019) and BCS 4.0 (OR = 5.79, 95% CI: 1.34- 31.7, p = 0.026). Results highlighted the importance of good nutrition that ensures cows achieve a BCS of at least 3 (scale: 1-5) before breeding.